How has dental pulp stem cells isolation been conducted? A scoping review - Camila Perelló Ferrúa; Eduarda Gervini Zampieri Centeno; Laísa Camerini da Rosa; Cainá Corrêa do Amaral; Rafaely Ferreira Severo; Rafael Sarkis-Onofre; Gustavo Giacomelli Nascimento; Gabriele Cordenonzi; Rachel Krolow Bast; Flávio Fernando Demarco; Fernanda Nedel (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: The objective of this study was to realize a scoping review the literature in order to identify the profile of DPSCs isolation and analyze the possible risk factors that could change the native behavior of these cells. An initial search was conducted using the following MeSH terms: "(dental pulp stem cell [MeSH])"; "(dental pulp [MeSH])" AND "(stem cell [MeSH])"; "("dental pulp stem cell" [MeSH]")". The electronic search was done without date restriction up to and including April 2014, in PubMed, Scopus, Scielo and ISI Web of Knowledge databases. Studies were submitted to inclusion and exclusion criteria and 222 articles were included. Data showed that over the past 15 years many studies have been conducted using DPSCs. However this is the first systematic review regarding the isolation of stem cell, and more specifically of dental pulp stem cells. The isolation of dental pulp stem cells showed great variability, hampering the development of standard protocols to achieve in vitro dental pulp stem cells with similar characteristics. This scoping review combined, for the first time, the methodologies used for dental pulp stem isolation, highlighting the most frequently used.